Zirconacyclopentadiene-Annulated Polycyclic Aromatic Hydrocarbons (ZrPAHs) - Kiel, Gavin R. (Angew Chem Int Ed Engl, 2017)
Syntheses of large polycyclic aromatic hydrocarbons (PAHs) and graphene nanostructures demand methods capable of selectively and efficiently fusing large numbers of aromatic rings, yet such methods remain scarce. Here we report a new approach, based on the quantitative intramolecular reductive cyclization of an oligo(diyne) with a low-valent zirconocene reagent, which gives a PAH with one or more annulated zirconacyclopentadienes (ZrPAH). The efficiency is demonstrated by a high-yielding, five-fold intramolecular coupling to form a helical, sixteen-fused-ring ZrPAH (from a precursor with no fused rings). Several other PAH topologies are also reported. Protiodemetallation of the ZrPAHs allowed full characterization (including by X-ray crystallography) of PAHs containing one or more appended dienes possessing the o-quinodimethane (o-QDM) structure, which are usually too reactive to isolate and are potentially valuable for fusion of more rings via Diels-Alder reactions.